PRESIDENT PRATIBHA PATIL’S POLITICAL JOURNEY: AN ICON OF WOMEN’S LEADERSHIP - Chahande, Pranita; Rathod, Vimal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper reviews the political journey of India’s first woman President Pratibha Devisingh Patil, highlighting her rise from a small village in Maharashtra to the highest constitutional office in the country. As a pioneer in women’s leadership, her career reflects significant milestones in Indian politics, particularly in promoting equality and representation in a patriarchal culture. This study examines her contributions as a jurist, minister, governor and president, focusing on her role in empowering women, promoting education and advocating for social welfare. It also considers the symbolic significance of her presidency in challenging traditional patriarchal cultural roles in a predominantly patriarchal political system. While acknowledging the criticisms and controversies of her tenure, this paper highlights her enduring legacy as a pioneer for women in public life. By analysing her political journey and leadership style, this research provides insights into the evolving landscape of women’s political participation in India.